Karakteristik Aktivitas Pedagang Kaki Lima di Ruang Kota (Studi Kasus: Kawasan Pendidikan Tembalang, Kota Semarang) - Widjajanti, Retno (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The paper examines the characteristics of street vendors (Pedagang Kaki Lima – PKL) in the urban space by case study in Tembalang educational area in Semarang City. The study employs quantitative method and applies positivistic paradigm in constructing its conclusion. Nowadays, activities in Indonesian cities tend to be dualistic, namely formal and informal; be it in the physical appearance, or in its social-economic and social-cultural. Tembalang, as one of Semarang city’s fast growing area due its role as educational center also experiences the dualism, marked by the increasing activity of formal sector in the form of stores providing goods and services and at the same time informal sector in the form of PKL. On the one hand, this rapid development occurs in a functional area which has not accommodated PKL activities in its planning. As a result, this spontaneous and unplanned development has the potential to cause various urban problems in the future. On the other hand, their presence has helped provide the local community, especially students of their daily needs with advantages in terms of location proximity and affordability, especially when compared to goods and services provided by the formal sector.